1994
DOI: 10.1103/physrevlett.72.156
|View full text |Cite
|
Sign up to set email alerts
|

Optical probes of excited states in poly(p-phenylenevinylene)

Abstract: We have studied electronic excited states in films of poly(p-phenylenevinylene) using picosecond transient and cw photomodulation, photoluminescence, and their excitation spectra, as well as electroabsorption spectroscopy. %'e have determined all the important energy levels of singlet excitons with odd and even parity, the onset of the continuum band, the two-electron (biexciton) states, and the two relevant triplet states, and show that good agreement exists with models involving electron correlation. PACS nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(150 citation statements)
references
References 25 publications
6
143
1
Order By: Relevance
“…It has previously been reported that the EA response of MEH-PPV in this energy region was not matched by any feature in the derivative spectra. 11, 21 Liess et al 11 reported that similar features are present in the EA spectra of several luminescent conjugated polymers ͓͑dioctyloxy͒-PPV ͑DOO-PPV͒ and poly͑alkyl thiophene͒ ͑PAT͔͒ but absent from that of nonluminescent polymers ͑PTV, PDA͒ and speculated that it is due to a high-energy A g state, and that its prescence is characteristic of luminescent polymers. We see no evidence for such a feature in the EA spectrum of PPV, which is lumines- cent.…”
Section: B Electroabsorption Spectramentioning
confidence: 81%
See 1 more Smart Citation
“…It has previously been reported that the EA response of MEH-PPV in this energy region was not matched by any feature in the derivative spectra. 11, 21 Liess et al 11 reported that similar features are present in the EA spectra of several luminescent conjugated polymers ͓͑dioctyloxy͒-PPV ͑DOO-PPV͒ and poly͑alkyl thiophene͒ ͑PAT͔͒ but absent from that of nonluminescent polymers ͑PTV, PDA͒ and speculated that it is due to a high-energy A g state, and that its prescence is characteristic of luminescent polymers. We see no evidence for such a feature in the EA spectrum of PPV, which is lumines- cent.…”
Section: B Electroabsorption Spectramentioning
confidence: 81%
“…Both agree well with previous reports. 1,11,[21][22][23] The PPV spectrum consists of two strong peaks, labeled I and III, at 2.84 and 6.15 eV, and a third, weaker, peak II, at 4.77 eV. At around 3.66 eV the slope of peak I changes, suggesting that there are at least two overlapping components contributing to peak I.…”
Section: A Linear Absorption Spectramentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21] For example, in polydiacetylene, the primary excitation is a neutral exciton with strong exciton binding energy. 10,11 In contrast, the primary excitation in poly(p-phenylenevinylene) (PPV) and its derivatives is debated to be a neutral exciton [12][13][14][15][16][17] or a charged polaron. [18][19][20][21] By contrast, chemically doped conjugated polymers, which show high electrical conductivity at room temperature, have clearly charged defect (polaron) states that are extrinsically introduced in the bandgap by chemical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This results in bleaching of the allowed absorption and the appearance of induced absorption bands in the EA spectrum. [13][14][15][16][17][18][19] Samples were mounted in a cold-finger liquid nitrogen cryostat equipped with optical and electrical access. A sinusoidal electric field modulated at 5 kHz was applied to the sample using the reference output of a lock-in amplifier driving a high voltage amplifier.…”
Section: Experimental Methodsmentioning
confidence: 99%